Awareness and practices of cervical cancer screening among women in Rajnandgaon district, central India: health education is the need of the hour - Armo, Meena; Khunte, Vimal; Sainik, Siddhi; Kanniga G., Rohini; Jatwar, Nandani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cervical cancer is a leading cause of morbidity and mortality among rural women in India. Early screening has been shown to be the most effective measure to prevent the disease. However, lack of awareness, lack of infrastructure, social stigma and fear are barriers to cervical cancer screening. The study was undertaken to assess the knowledge and practice among rural women regarding cervical cancer and screening tests with the aim of helping health professionals to revise policies and practices. Methods: It was a cross-sectional questionnaire-based study, conducted from January 2018 to September 2018 in the Department of Obstetrics and Gynecology at Government Medical College Rajnandgaon. A tertiary care hospital located in the southwest Chhattisgarh. A total of 506 women aged 21-65 years were included and assessed. Qualitative data were presented as frequencies and percentages by using SPSS version 21. Results: Of the total 506 respondents, 15.41 % had heard of cervical cancer, while 8.1% about cervical cancer screening. Unfortunately, only 1.2% women were ever been screened by Pap test. Although importance of screening had been thoroughly explained to the respondents, despite the fact only 57.1% showed willingness to undergo cervical cancer screening in the future. However, 63.9%women having gynecological complains were significantly associated with better attitude towards future cervical cancer screening than women without having gynaecological complains. Conclusions: Awareness and practice of the screening for cervical cancer was very poor in the rural population as well as in health care providers. Hence intensive health education is the need of the hour to change the scenario.